Las habilidades sociales y la autoestima en los estudiantes de séptimo grado paralelo a, de la escuela de educación básica municipal Borja, 2020-2021 - Segarra Iñiguez, Jennifer Cristina (2022)
The present investigative work called SOCIAL SKILLS AND SELF-ESTEEM IN SEVENTH GRADE STUDENTS PARALLEL TO, FROM A BORJA MUNICIPAL BASIC EDUCATION SCHOOL, 2020-2021, had as objective to investigate the relationship between social skills and self-esteem in seventh graders. A non-experimental, cross-sectional design was applied; with a quantitative approach and descriptive substantive type. The methods used were analytical, synthetic, hypothetical-deductive, inductive and statistical, as instruments the Goldstein Social Skills scale was obtained to identify the degree of development of social competence, it was possible to determine that the skills that seventh grade students have are few, especially in basic skills, related to feelings and alternatives to aggression with 39.13%, consequently there is no correct social interaction in the group studied, implying the need to reinforce skills such as listening, starting a conversation to avoid conflicts, among others, as a second instrument the Coopersmith Self-Esteem Inventory was reduced to know the level of acceptance of themselves, taking into account that it was thought to study a sample of 23 students, the exposed results that handled low self-esteem with a 21.74%, especially in social self-esteem, which indicates that they cannot aut or recognized or valued correctly, on the other hand, a large number of students have shown normal self-esteem. Relating the variables with the results, it is concluded that there is a relationship between social skills and self-esteem, insofar as having few social skills will trigger low self-esteem and vice versa, so it is recommended that the authorities of the School of Municipal Basic General Education Borja execute the psychoeducational proposal raised in the present investigation